PENDIDIKAN AKIDAH BAGI ANAK USIA DINI - Susiba Susiba (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
In the view of Islam children are a mandate for their parents. One of the obligations of parents to children is to provide akidah education from an early age. Because akidah has a big influence on children which influences and controls each child's actions and behavior. However, along with the changes in the structure of society has made parents unable to educate their children for all kinds of needs and skills as well as fostering their faith. The importance of religious education is given early, because this period will not be repeated again in the future. And religious life in childhood has a huge influence on the religious life of children in their adult years.